396 Knowledge, attitudes and behaviors of New Zealand physiotherapists to sports-related concussion. (3rd March 2020) - Reid, Duncan; Hume, Patria; Whatman, Chris; Theadom, Alice; Walters, Simon; Fulcher, Mark
Abstract : Background: An estimated 21% of all traumatic brain injuries (TBI) are sustained during sports participation. Physiotherapists are key practitioners in the health management of players that suffer sport related concussion (SRC) in New Zealand (NZ). Physiotherapists are often the only health professional available at community sports events to assess and manage acute concussion episodes and the sequelae. There is no previous research into the SRC knowledge, attitudes and behaviours of NZ physiotherapists Objective: To quantify SRC knowledge, attitudes and behaviours of NZ physiotherapists. Design: Cross-sectional observational study under institutional ethics (#16/187) using an anonymous electronic 45-item multi-choice questionnaire accessed via an email invitation link. Setting: The NZ Physiotherapy Community of 1, 179 registered physiotherapists were invited to participate. Patients (or Participants): There were 122 valid responses from registered physiotherapists (10% response rate). Interventions (or assessment of risk factors): The independent variables were SRC knowledge, attitude and behaviour items in the survey. Main outcome measurements: Analyses of percentage of responses to SRC knowledge, attitude and behaviour items in the survey was planned before data collection began. Results: Most participants worked in sports private practice (74%). The main area of sports engagement was rugby (45%). Physiotherapists displayed high levels of knowledge for common signs and symptoms (98%), recognition of SRC and factors that affect recovery (98%). They displayed good attitudes to referral to medical practitioners and return to play decisions. Sixty percent of participants had observed inappropriate coach and/or player behaviour linked to suspected SRC. Conclusions: Physiotherapists in this survey were very knowledgeable and showed positive attitudes towards correct management of SRC. They were very good at recognising key signs and symptoms and had good referral patterns to medical practitioners. They shared a strong desire to be more involved in side-line management and testing and wanted to see a multidisciplinary approach to return to play decision making.